2012
DOI: 10.1016/j.amjmed.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Sleep Duration, and Diabetes Mellitus: Analysis of the National Health Interview Survey

Abstract: Background Effect of race/ethnicity on the risk of diabetes associated with sleep duration has not been systematically investigated. This study assessed whether blacks reporting short (≤ 5 hours) or long (≥ 9 hours) sleep durations were at greater risk for diabetes than their white counterparts. In addition, this study also examined whether the influence of race/ethnicity on associations between abnormal sleep durations and the presence of diabetes were independent of individuals’ sociodemographic and medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 34 publications
5
82
3
Order By: Relevance
“…Indeed, our focus group participants revealed that they frequently compromised sleep and exercise to meet the demands of their lives, and sometimes used alcohol in excess to cope with their stressors. T2dm interventions will therefore need to emphasize the need for adequate sleep and moderation in alcohol consumption, since both are linked to t2dm-related health outcomes (Emanuele, Swade, & Emanuele, 1998;Knutson, Ryden, Mander, & Van Cauter, 2006;Zizi et al, 2012). Resiliencybased interventions may hold promise for Black men since they empower individuals to see stressful situations as challenges and thereby provide opportunities for personal growth, positively influencing t2dm-related outcomes (e.g., HbA1c, body mass index; Steinhardt, Mamerow, Brown, & Jolly, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our focus group participants revealed that they frequently compromised sleep and exercise to meet the demands of their lives, and sometimes used alcohol in excess to cope with their stressors. T2dm interventions will therefore need to emphasize the need for adequate sleep and moderation in alcohol consumption, since both are linked to t2dm-related health outcomes (Emanuele, Swade, & Emanuele, 1998;Knutson, Ryden, Mander, & Van Cauter, 2006;Zizi et al, 2012). Resiliencybased interventions may hold promise for Black men since they empower individuals to see stressful situations as challenges and thereby provide opportunities for personal growth, positively influencing t2dm-related outcomes (e.g., HbA1c, body mass index; Steinhardt, Mamerow, Brown, & Jolly, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this knowledge comes from animal models of sleep deprivation (1) and from short-term experimentally induced sleep deprivation in humans, where deficits in cognition, vigilance, memory, mood, behavior, ability to learn, immune function, and general performance (6,24) have been identified. Self-reported short sleep duration in epidemiological studies has also been associated with longterm outcomes such as diabetes (25)(26)(27), obesity, depression (28), hypertension (29), and all-cause mortality (10), with at least some studies showing the elderly being particularly susceptible (30). Underlying mechanisms to explain the potential relationship between short sleep duration and the development of chronic diseases may be through the development of obesity (31)(32)(33)(34) or proinflammatory states (35).…”
Section: Short Sleep Durationmentioning
confidence: 99%
“…11,12 However, the mechanisms behind these associations remain elusive. It is unclear whether environmental changes such as increased stress lead to a change in sleep patterns and thus increased risk to disease, or whether there are shared biological mechanisms between sleep regulation and a range of diseases.…”
Section: Introductionmentioning
confidence: 99%